Pengembangan Media Pembelajaran Kuliner Etnis Sulawesi Selatan bagi Mahasiswa Program Studi Vokasi Perhotelan - Dewi Andriani; St. Hadijah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
The purpose of this study was to test the feasibility of learning media of Indonesian Gastronomy and Culinary Studies and to describe the responses of media and material experts on learning media developed. This research method used research and development with a 4-D model including define, design, develop and disseminate. Data collection techniques used observation, interview and questionnaire involving media experts, material experts and hospitality study program students. The data analysis technique used qualitative and quantitative analysis which described the quality of the media and material based on the questionnaire assessment of the expert team. The results of the study showed that the media expert produced an average value of 4.31 with an average validation result of the material expert of 4.73 and an average value for the results of the feasibility test questionnaire of 4.06. These results indicated that the value of the validation test from media and material experts stated that it was feasible and there was no need for a temporary revision of the feasibility test conducted on students in the Indonesian Gastronomy and Culinary class, showing a significant increase in terms of understanding the learning. These results were obtained after carrying out the second test. It can be concluded that the use of more varied learning media such as videos can improve learning outcomes.